HUBUNGAN ANTARA TINGKAT STRES DENGAN KEJADIAN POLYCYSTIC OVARY SYNDROME (PCOS) PADA REMAJA - Putri Anju Anjali; Rini Aryani (PT. Hasba Edukasi Mandiri, 2026)
Polycystic Ovary Syndrome (PCOS) is a hormonal disorder that often occurs in women of reproductive age, including adolescent girls. During adolescence, psychological stress tends to increase due to hormonal changes, academic pressure, and social factors, which are thought to play a role in the occurrence of PCOS. This study aims to determine the relationship between stress levels and the incidence of Polycystic Ovary Syndrome (PCOS) in female students at SMK Negeri 1 Demak. This study uses an analytical observational design with data collection carried out at one observation time and was implemented at SMK Negeri 1 Demak in January 2026. The research subjects were 149 female adolescents who were selected using consecutive sampling techniques. Stress levels were measured using the Perceived Stress Scale (PSS-10) questionnaire. The incidence of PCOS is determined based on the diagnostic criteria for PCOS in adolescents. Data analysis was carried out using the SPSS program including univariate and bivariate analysis with the chi-square test and contingency coefficient. The results of the study showed that most respondents experienced moderate stress (77.2%). PCOS was found in 50.3% of respondents. The results of the chi-square test showed that there was a significant relationship between stress levels and the incidence of PCOS (p = 0.001). The contingency coefficient value r = 0.411 indicates a moderate relationship. The conclusion of this study is that there is a significant relationship between stress levels and the incidence of Polycystic Ovary Syndrome (PCOS) in adolescents.